Legislasi Undang-Undang Nomor 23 Tahun 2004 tentang Penghapusan Kekerasan dalam Rumah Tangga dan Relevansinya dengan Hukum Islam - Wahyu, Ramdani (Al-Manahij: Jurnal Kajian Hukum Islam, 2008)
UU no. 23 th. 2004 about domestic violence demolishing is intended to prevent the violence in domestic area. Based on Islamic syariah, the forbidding about violence to woman is already in line to the Islamic law.